Analysis of HDF curves for the formation of functional dependence in the wider area of the Republic of Srpska - Praštalo Petar R. (Savez inženjera i tehničara Srbije, 2021)
In hydrotechnical practice, there is a great need to use precipitation data in the wider area of the area where the research is being done. The lack of precipitation stations that can register shorter-duration rainfall, less than 24 hours, poses a huge problem for Engineers in practice. Based on this work, an analysis of existing precipitation data is used to create a functional dependence on the wider region based on the available data. Thus formed functional dependency facilitates the solving of a large number of hydrotechnical problems. This work shows the formation of a mathematical model based on MS.